Analysis of business behavior and HRM perspectives on post-COVID-19 SME business sustainability - Nuraini Asriati; S. Syamsuri; Munawar Thoharudin; Sandra Fitria Wardani; Aditya Halim Perdana Kusuma Putra (Cogent Business & Management, 2022)
There are not many studies that examine business continuity and business strategy combined with business people's psychological and psychological approaches. This study relates the elaboration between the HRM, strategic management, and business management fields analyzed with a quantitative approach. This study involved 100 respondents of handicraft business actors at the border between Indonesia and Malaysia. The data collection method used a survey method. Data processing uses the Structural Equation Model (SEM-PLS) approach in the SMART-PLS. This research study states that through direct relationship, all demonstration variables have a positive and significant effect. Meanwhile, the demonstration of the relationship between variables states that there are two patterns of relationship that do not have a significant effect. Through a combination of human resource management variables, business strategy, creativity, entrepreneurship capability, and SME sustainability perceived, packaged with a planned behavior theory (TPB) approach, several main research findings conclude. First, our study indicate that business sustainability can be achieved if an optimal business strategy (BS) has been realized by forming good entrepreneurial capabilities. Second, the role of antecedent human resource locus of control (HR) is a variable that has complete control in creating the creativity of small-medium enterprise actors and creating entrepreneurial capabilities.
Keywords: O15; M11; M20; J24; 650; SME; business strategy; business sustainability; Human resources management; planned behavior theory